Directive Speech Acts and Hedges Presented by Female Main Characters of Jane Austen’s Novels - Suryanovika, Citra; Julhijah, Novita (Lingua Cultura, 2018)
This research aimed at identifying the category of directive speech acts found in the utterances of six female characters of six Jane Austen’s novels (Elinor Dashwood of Sense and Sensibility, Elizabeth Bennet of Pride and Prejudice, Fanny Price of Mansfield Park, Emma Woodhouse of Emma, Anne Elliot of Persuasion, and Catherine Morland of Northanger Abbey), and explaining the hedges used in directive speech acts. The research employed a descriptive qualitative method to collect, analyze, and discuss the findings which closely related to the classification of directive speech acts of female main characters in Jane Austen’s novels and the use of hedges in directive speech acts. The findings show that directive speech acts are formed imperatively, declaratively, and interrogatively. From all existing categories of directive speech acts (ask, order, command, request, suggestion, beg, plead, pray, entreat, invite, permit, and advise), the female main characters in Jane Austen’s novels only presents ask, request, advice, and suggestion. Hedges found in directive speech acts are not only used to show hesitancy but also to present certainty (I believe, I must) of the speakers’ previous knowledge. In addition, hedges are not the only marker that may show uncertainty, because exclamation ‘well!’ and ‘oh!’, as well as the contrasting conjunction are used to pause due to the uncertain statement.